Dominance and Frequency of Mite Species Associated with Poultry Droppings - Al-Kubaisi, Fatima M. A.; Al-Dulaimi, Sabah I. H. (Iraqi Journal of Science, 2020)
The present study was carried out onAl-Saqlawiya poultry farm’s soil (Anbar, Iraq) for the period of 8 months (November 2018- June 2019). A total of 75 samples of poultry droppings were collectedrandomly. 552 individuals of mite,belonging to 3 orders and 8 families representing 15 species, were found. These species were: Acarus gracilis, Acarus siro, Caloglyphus berlesi, Androlaelaps casalis, Sejus temperaticus, Parasitus paraconsanguineus, Eugamasus butleri, Macrocheles medarius, Macrocheles glaber, Macrocheles muscaedomesticae, Macrocheles matrius, Kleemannia plumosus, Cheyletus eruditus, Cheyletus malaccensis, and Pyemotes herfsi. The highest population density belonged to order Astigmata, followed by orders Mesostigmata and Prostigmata, respectively. The dominance and frequency of mite species were linked to the availability of appropriate conditions in terms of food source and temperatures registered in theIraqi Meteorological Directorate. Thehighest mite population densities were recorded during the winter months compared to the summer months.